The cabbage-leaf water extract can inhibit the germination and seedling growth of three receptor crops - Zhao, Cong; Ye, Meihua; Pan, Ting; Zhao, Min; Li, Nana; Xu, Yueyue; Huang, Xuefang; Wang, Juanling (Frontiers in Plant Science, 2025)
Cabbage cultivation has been observed to significantly hinder the growth of subsequent crops in the cold, arid regions of Shanxi Province. To investigate the allelopathic effects of cabbage (Brassica oleracea L. var. Capitata L.) on seed germination and seedling growth of three crops commonly cultivated in such areas, we studied the effects of water extracts from air-dried cabbage leaves on cocozelle, kidney bean, and corn. Experiments were conducted using both petri dish filter paper and pot culture methods to simulate natural conditions. The results indicated that cabbage leaf water extracts at concentrations of 0.01-0.04 g·mL-1 significantly inhibited seed germination. At higher concentrations (0.06-0.08 g·mL-1), the extract markedly suppressed seedling growth in all three crops (p < 0.05), with the degree of inhibition increasing alongside concentration. Radicle elongation in cocozelle and corn was more strongly inhibited than germ elongation at the same extract concentration, In contrast, kidney bean showed greater inhibition of germ elongation than radicle elongation at 0.04 g·mL-1. Malondialdehyde (MDA) content was elevated in kidney bean and corn seedlings treated with cabbage extract, indicating oxidative stress. At extract concentrations of 0.06-0.08 g·mL-1, antioxidant enzyme activities, such as antioxidase superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) were enhanced in all three crops. The comprehensive allelopathic inhibition followed the order: cocozelle > corn > kidney bean. The differences appear to be related to the changes in MDA content and antioxidant enzyme activity. Based on these findings, rotating cabbage and kidney bean may help reduce negative allelopathic effects. It is also recommended to remove the entire aboveground portion of cabbage during harvest to reduce allelochemical residues in the soil and minimize their inhibitory impact on subsequent crops.